2Hz-electroacupuncture attenuates heroin-seeking behaviors via adjusts CB1-Rs and CB2-Rs expression in relapse-relevant brain regions of heroin self-administration rats - Chen, L; Gong, X-K; Leng, C-L; Ma, B-M; Ru, Q; Xiong, Q; Yue, K; Zhou, M; Tian, X; Li, C-Y; Wu, Y-X (Physiological research, 2019)
Opiate addiction has a high rate of relapse. The accumulating evidence shows that electroacupuncture (EA) may be effective for the treatment of opiate relapse. However, the change of expression of CB1-Rs and CB2-Rs involve in 2Hz EA anti-relapse pathway is still unclear. To explore the changes of expression of CB1-Rs and CB2-Rs, heroin self-administration (SA) model rats were adopted and treated using 2Hz EA. The expressions of CB1-Rs and CB2-Rs were observed using immunohistochemistry method. The results showed that, compared with the control group, active pokes in the heroin-addicted group increased, while the active pokes decreased significantly in 2Hz EA group compared with heroin-addicted group. Correspondingly, the expression of CB1-Rs in prefrontal cortex (PFC), hippocampus (Hip), nucleus accumbens (NAc) and ventral tegmental area (VTA) all increased significantly while the expression of CB2-Rs in those relapse-relevant brain regions decreased obviously in heroin-addicted group when compared with the control group. In addition, the expression of CB1-Rs obviously decreased in the 2Hz EA group while the expression of CB2-Rs in those relapse-relevant brain regions increased significantly when compared with the heroin-addicted group. It indicated that 2Hz EA could attenuate the heroin-evoked seeking behaviors effectively. The anti-relapse effects of 2Hz EA might be related to the decrease of CB1-Rs and increase of CB2-Rs expression in relapse-relevant brain regions of heroin SA rats.
Keywords: závislost na heroinu; recidiva; Narcotic Antagonists; heroin; signální transdukce; Heroin Dependence; Signal Transduction; extinkce (psychologie); mozek; elektroakupunktura; chování zvířat; chování při shánění drogy; lokomoce; narkotika - antagonisté; Receptor, Cannabinoid, CB2; Extinction, Psychological; Heroin; Self Administration; receptor kanabinoidní CB2; zvířata; Drug-Seeking Behavior; autoaplikace; potkani Sprague-Dawley; Male; receptor kanabinoidní CB1; Brain; Recurrence; Locomotion; Rats, Sprague-Dawley; Animals; Receptor, Cannabinoid, CB1; mužské pohlaví; Disease Models, Animal; Behavior, Animal; Electroacupuncture; modely nemocí na zvířatech